Comparison of corrosion resistance of a Fe-Mn-Al alloy boronized by pack or salt bath process - Casteletti, Luiz Carlos [UNESP]; Heck, Stênio Cristaldo [UNESP]; Picon, Carlos Alberto [UNESP]; Tremiliosi-Filho, Germano; Neto, Amadeu Lombardi (My University, 2010)
Fe-Mn-Al alloys have been developed to replace traditional stainless steel in some applications, in less severe corrosive environments. In this work, an alloy of this class was subjected to two different boronizing treatments, aiming to verify the influence of these treatments on the hardness and sea water corrosion resistance of this alloy. The boronizing treatment was carried out using liquid and powder medium. The layer formed in liquid medium was harder but thinner. The sample boronized by salt bath process presented the biggest corrosion potential and the smallest corrosion current, followed by the pack boronized and the un-treated alloy. Copyright © (2010) by Associação Brasileira de Metalurgia Materiais e Mineração (ABM).
Keywords: Boronizing; Corrosion; Fe-Mn-Al; Pack; Salt bath